Predictive factors of subsequent insulin requirement for glycemic control during pregnancy at diagnosis of gestational diabetes mellitus. Issue 3 (11th January 2019) - Ducarme, Guillaume; Desroys du Roure, François; Grange, Joséphine; Vital, Mathilde; Le Thuaut, Aurélie; Crespin‐Delcourt, Ingrid
Abstract: Objective: To determine maternal and biological parameters at diagnosis of gestational diabetes mellitus (GDM) as predictors of antenatal insulin therapy (AIT) for glycemic control. Methods: In this planned secondary analysis of a prospective observational study, we recruited women diagnosed with GDM between July 1, 2014, and October 31, 2015. Maternal and biological parameters were analyzed as predictors of AIT using multivariable logistic regression analyses. Predictive accuracy of a cut‐off value for a biological predictor was determined using the area under the receiver operating characteristic curve (AUC) and the Youden index (J). Results: Of 200 women included (mean gestational age 22 ± 6 weeks), 72 (36%) required AIT. No maternal characteristic was associated with AIT. Glycated hemoglobin (HbA1c; adjusted odds ratio [aOR] 3.15, 95% CI 1.03–9.69) and elevated 1‐hour oral glucose tolerance test (OGTT; aOR 1.23, 95% CI 1.13–1.46) were predictors of AIT. Analyses suggested inaccurate prediction of AIT, with an optimal cut‐off HbA1c value of 5.4% (J=0.14; AUC 0.58, 95% CI 0.48–0.67), and an optimal 1‐hour plasma glucose OGTT value of 1.77 mg/dL (J=0.24; AUC 0.62, 95% CI 0.50–0.74). Conclusion: HbA1c at diagnosis of GDM and elevated 1‐hour OGTT were independent predictors of AIT for glycemic control. Clinicaltrials.gov: NCT02159378. Abstract : Glycated hemoglobin level at diagnosis of gestational diabetes mellitus and elevated 1‐hour oral glucose tolerance test were independent predictors for subsequent insulin requirement during pregnancy.